2011
DOI: 10.1172/jci44228
|View full text |Cite
|
Sign up to set email alerts
|

BVES regulates EMT in human corneal and colon cancer cells and is silenced via promoter methylation in human colorectal carcinoma

Abstract: The acquisition of a mesenchymal phenotype is a critical step in the metastatic progression of epithelial carcinomas. Adherens junctions (AJs) are required for suppressing this epithelial-mesenchymal transition (EMT) but less is known about the role of tight junctions (TJs) in this process. Here, we investigated the functions of blood vessel epicardial substance (BVES, also known as POPDC1 and POP1), an integral membrane protein that regulates TJ formation. BVES was found to be underexpressed in all stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(107 citation statements)
references
References 53 publications
7
99
0
1
Order By: Relevance
“…A report, published while this manuscript was in preparation, demonstrated that claudin-5 is decreased in bleomycininduced pulmonary fibrosis (39), which indicated that decreased CLDN5 expression may be involved in epithelial-mesenchymal transition (EMT). EMT often involves promoter methylation to turn off epithelial genes (40,41). The hypermethylation of claudin-5 in IPF lung tissues could be an indicator of EMT occurring in specific cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…A report, published while this manuscript was in preparation, demonstrated that claudin-5 is decreased in bleomycininduced pulmonary fibrosis (39), which indicated that decreased CLDN5 expression may be involved in epithelial-mesenchymal transition (EMT). EMT often involves promoter methylation to turn off epithelial genes (40,41). The hypermethylation of claudin-5 in IPF lung tissues could be an indicator of EMT occurring in specific cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…In mice treated with NS, Lipo, or Lipo ϩ NC shRNA, measurable endometrial fragments after a 25-day incubation were observed, with an average volume of 28.36, 18.17, and 19.74 mm 3 , respectively (Fig. 8, A and F).…”
Section: Anxa2 Knockdown Compromises Growth Metastasis and Proangiomentioning
confidence: 98%
“…Epithelial to mesenchymal transition (EMT) 1 is a process characterized by a loss of polarity of epithelial cells and transition to a mesenchymal phenotype (3). It has been reported both under physiological situations like wound healing (4) and during development as well as in malignant cells undergoing invasion and metastasis, which could be initiated through a variety of stimuli, including hormonal turbulence, genetic mutation, or hypoxia (5).…”
mentioning
confidence: 99%
“…BVES is another transmembrane component of tight junctions that is downregulated during the epithelial-to-mesenchymal transition (EMT) (Han et al, 2014;Williams et al, 2011). Reexpression of BVES in colorectal cancer cells is sufficient to repress proliferation and metastasis, indicating that it also has tumour suppressive activities.…”
Section: Regulation Of Cell Behaviour and Survival By Transmembrane Pmentioning
confidence: 99%